แอปพลิเคชันช่วยในการตรวจสอบคุณภาพสำหรับกระบวนการก่อสร้าง (ระบบส่วนหน้าบ้าน) - คีตาภัทร วงษาเนาว์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Presently, the communication via the application such as LINE has been widely used— not only among individuals, but also in large scale organization. Although the benefits are noticeably seen, the communication via these application and internet still have some relevant limitations. For instance, miscommunication, misunderstanding the context, mis-send to the targeted person, and even ignorance/negligence of the received context. Accordingly, we have realized the problems and intended to develop the "Construction process quality control assisted application (front end)" to solve various underlying communication issues. Requirement was gathered from users of three main industrial companies for 5 times including 1 visit at Department of Highways, 2 visits at Team built Co., Ltd., and 2 visits at Prinsiri Co., Ltd. The received information was then analyzed for appropriate features that are beneficial to users. After summarizing the requirements, user interface was designed using Adobe XD in order to create the application’s prototype and receive users’ feedback for better improvement before developing the application. Upon developing, JavaScript with VScode through the framework called React Native and Expo is used due to high compatibility in both iOS and Android operating systems. Upon developing, users’ feedback and needs are constantly updated and utilized to best improve the application. User testing was then executed with 13 real users—project manager and foreman positions—from Team built Co., Ltd and Prinsiri Co., Ltd., whom have claimed great satisfaction.